Reversão das alterações comportamentais e marcadores de dano oxidativo (estado redox) pelo dimetil fumarato no cérebro de camundongos submetidos ao modelo de mania induzido por anfetamina - Cavalcante, Talita Matias Barbosa (2023)
Bipolar disorder (BD) is a chronic, disabling disease, with high rates of morbidity and mortality, suicide and 2% of the world's population is affected. The pathophysiology involves several pathways and the available treatment is considered unsatisfactory, making it necessary to screen new drugs for treatment, with the amphetamine-induced mania (ANF) model being used to screen new substances with therapeutic potential in BD. Dimethyl fumarate (DMF) acts through a pathway that depends and does not depend on the activation of Nfr2 and has a beneficial effect on the central nervous system (CNS). Thus, the objective was to investigate the antioxidant molecular mechanisms involved in this effect through the experimental model of the manic phase of BD induced by (ANF). The animals received treatment with saline, lithium or DM (60-120 mg/kg) from the 8th day of amphetamine administration. On the 14th day, the animals were subjected to behavioral tests to evaluate locomotor activity (Open field test), self-care capacity (Spray test), cognitive evaluation (New object recognition test and Y maze), evaluation of risk (elevated plus maze test) and brain dissection to evaluate neurochemical parameters. The concentrations of GSH, enzymatic activity of SOD and catalase in the hippocampus and striatum were evaluated using ELISA. Furthermore, the expression of cleaved caspase-3 and phospho-Nrf2 in the hippocampus was evaluated using immunofluorescence analysis. The results demonstrated a reduction in locomotor hyperactivity in the DM groups (60 and 120 mg/kg), an increase in self-care behavior (DM 60 and 120 mg/kg), a reduction in anxious and exploratory behavior (DM 60 and 120 mg/kg) in addition reduction in cognitive deficit (DM 60 and 120mg/kg) when compared to the ANF group alone. Increased GSH (DM 60 and 120 mg/kg) in the hippocampus, increased expression of cleaved Caspase 3 in hippocampal subareas induced by ANF, reversal by LIT and DM120. Immunofluorescence for Nrf2 in the hippocampus did not demonstrate changes in the groups evaluated. Therefore, the findings suggest that the mechanisms involved in the antimanic effect of DMF are through the Nrf2-independent antioxidant and neuroprotective pathway. In this sense, the data found corroborate the antioxidant activity of DM in the manic phase of BD induced by ANF in mice, contributing to research into screening new drugs for the treatment of the manic phase of BD.